An Analysis of English Speaking Syllable Words Stress Errors by The Students of English Education Study Program of University of Bengkulu - Ronaldi Styvant; Arasuli -; Rudi Afriazi (Universitas Bengkulu, 2019)
This research was aimed at finding out the errors of English speaking syllable stress by the students of English Education Study Program, University of Bengkulu. The subject of this study was 19 students with highest GPA and speaking and Phonetic phonology score or both of them of English Program. The method of data collection was recorded. The data were collected by recording their pronunciation in reading words stress and Audacity program to analysze the data. The result of this research showed that English Students pronunced syllable words stress in the first syllable and second syllable with average predicate and 2 stresses in a word with low predicate. Meanwhile, this research also found that a lot of students put the stress on the first syllable.